2005
DOI: 10.1159/000089523
|View full text |Cite
|
Sign up to set email alerts
|

Association of E-Cadherin Gene 3’-UTR C/T Polymorphism with Primary Open Angle Glaucoma

Abstract: Purpose: E-cadherin (E-CDH) is one of the most important cell surface glycoproteins involved in cell morphogenesis. In primary open angle glaucoma (POAG), the extracellular matrixes of trabecular meshwork and lamina cribrosa in the optic nerve head are out of balance. We suspected that E-CDH by way of metalloproteinases is closely related to POAG. We therefore investigated the relationship between CDH-1 gene 3′ untranslated region (3′-UTR) polymorphism and POAG patients in order to support this hypothesis. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…For rs1801026, whereas the allele T frequency was similar in POAG patients, in control subjects, it was much lower in our study (17.4%) than in the original study (52.4%). 20 However, our results in control subjects are very close to statistics in the dbSNP database for Asians (16.7%). As for rs1801270, association with POAG had not been replicated in two studies of Caucasians.…”
Section: Discussionsupporting
confidence: 83%
“…For rs1801026, whereas the allele T frequency was similar in POAG patients, in control subjects, it was much lower in our study (17.4%) than in the original study (52.4%). 20 However, our results in control subjects are very close to statistics in the dbSNP database for Asians (16.7%). As for rs1801270, association with POAG had not been replicated in two studies of Caucasians.…”
Section: Discussionsupporting
confidence: 83%
“…Although the function of the 3 0 -UTR C54 C/T polymorphism was unclear, studies have showed that this polymorphism was associated with cancer and other diseases (Tsai et al 2003, Wu et al 2005, Lin et al 2006. Wu et al found that the 'CC' homozygote indicates a relatively higher risk for developing prostate cancer than other genotypes (Lin et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although the function of the 3 0 -UTR C54 C/T polymorphism was unclear, studies have showed that this polymorphism was associated with cancer and other diseases (Tsai et al 2003, Wu et al 2005, Lin et al 2006. Wu et al found that the 'CC' homozygote indicates a relatively higher risk for developing prostate cancer than other genotypes (Lin et al 2006). Our study also showed that the frequency of the 'CC' homozygote in endometriosis patients (57.9%) was higher than that in controls (43.4%) and the 'CC' homozygote carriers had a higher incidence of developing endometriosis (1.79-fold) than those who do not.…”
Section: Discussionmentioning
confidence: 99%
“…T SNP (rs1801026) at nucleotide 2797 of the CDH1 cDNA is located 54 nucleotides downstream from the TAG stop codon [12] and are associated with risk of prostate cancer and primary open angle glaucoma, but these studies did not examine a large cohort of individuals [12,13]. Our previous study, using a large cohort of samples showed the 3 0 -UTR þ54C/T polymorphism of CDH1 was associated with the epithelial ovarian cancer and endometriosis development in Chinese Abbreviations: PCR, polymerase chain reaction; RFLP, restriction fragment length polymorphism; ESCC, esophageal squamous cell carcinoma; GCA, gastric cardiac adenocarcinoma; NSCLC, nonsmall-cell lung cancer; CDH1, E-cadherin gene; SNP, single-nucleotide polymorphisms; TNM, tumor-node-metastasis; FIGO, International Federation of Gynecology and Obstetrics.…”
Section: Introductionmentioning
confidence: 99%